Smart temperature control for agriculture through personal computer by RS232 channel / Mohd Noor Mohd Ghafar - Mohd Ghafar, Mohd Noor (2003)
Interactive manufacturing process, computer control is often needed to coordinate the component in the process control system. Nowadays, the digital computers have become more compact and cheaper; they are used as integral parts of industrial processes and modern manufacturing. It is essential in such industrial operations as controlling pressure, temperature and flow in the industries area. This project was developed with the use of a personal computer through Local Area Network to control electrical appliances using smart control switching that can be used especially in herbal plantation. By implementing this system, the heat detected from soil can be monitored. The hardware and software are interfaced with RS232 channel and a basic programming language. Visual Basic has been chosen as the programming language. The software design also include by Graphical User Interface (GUI).